The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1055/s-0040-1721162
|View full text |Cite
|
Sign up to set email alerts
|

Leclercia adecarboxylata Causing Spontaneous Bacterial Peritonitis in a Child with Nephrotic Syndrome: A Case Report and Review of Literature

Abstract: Infection is an important complication of childhood nephrotic syndrome (NS) and spontaneous bacterial peritonitis (SBP) is a frequently encountered one. We present a 7-year-old boy with NS who had decreased urine output, generalized body swelling, and abdominal pain. Urine analysis showed proteinuria of 50 mg/m2/d. Ascitic tap showed total leukocyte count of 100 cells/mm3, sugar of 67 mg/dL, and protein of 1.1 g/dL. Gram stain revealed gram-negative bacilli with pus cells and culture grown Leclercia adecarboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…In 2019, Spiegelhauer et al reported a literature cases review demonstrating its pathogenicity in 74 patients [5]. The majority of these cases had been reported in immunocompromised patients, unlike our patients where the 5 of 6 were immunocompetent; only one patient was considered as immunocompromised following kidney transplantation, although peritoneal dialysis could explain this infection episode given the high prevalence of infections in these patients [7,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…In 2019, Spiegelhauer et al reported a literature cases review demonstrating its pathogenicity in 74 patients [5]. The majority of these cases had been reported in immunocompromised patients, unlike our patients where the 5 of 6 were immunocompetent; only one patient was considered as immunocompromised following kidney transplantation, although peritoneal dialysis could explain this infection episode given the high prevalence of infections in these patients [7,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 61%
“…L. adecarboxylata is implicated in cases which involve endocarditis [15,16], catheterrelated bacteremia [10,17,18], bacteremia and cellulitis [5,6,9,19,20], urinary tract infections [6,21], pneumonia [5,22] and bacterial peritonitis, especially in peritoneal dialysis patient [7,[11][12][13][14], which was the case for the majority of our clinical presentations. L. adecarboxylata was most often found as a monomicrobial infection in immunocompromised patients, and as part of a polymicrobial infection in immunocompetent patients [5,12].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…A few cases with diabetes as the only risk factor have L. adecarboxylata infection of the skin and soft tissues[ 81 , 82 ]. L. adecarboxylata has been implicated in endocarditis[ 6 ], catheter-associated bacteremia[ 78 ], bacteremia, sepsis[ 3 , 67 ], septic arthritis, meningitis[ 83 ], cellulitis[ 2 , 84 ], urinary tract infections[ 85 ], pneumonia[ 70 ], and bacterial peritonitis, especially in patients on peritoneal dialysis[ 86 ]. Of these, the most common clinically are catheter-associated male urinary tract infections (translocation through the genitourinary tract), followed by ventilator-associated pneumonia, peritoneal dialysis peritonitis, corneal abscesses, vascular graft infections (entry into the infected host via catheter or wound)[ 87 ], and intestinal translocation (translocation of bacteria through the mucosal barrier of the gastrointestinal tract, presumably gastrointestinal bacteremia)[ 2 , 70 ].…”
Section: Discussionmentioning
confidence: 99%